Stress perturbation caused by multistage hydraulic fracturing: Implications for deep fault reactivation. (May 2021) - An, Mengke; Zhang, Fengshou; Dontsov, Egor; Elsworth, Derek; Zhu, Hehua; Zhao, Luanxiao
Abstract: Swarms of earthquakes during shale gas exploitation in the Changning area of Sichuan Basin indicate that hydraulic fracturing induces seismicity both within the target reservoir but also to depths of several kilometers below the horizontal well. These remote earthquakes are possibly triggered by total stress perturbations resulting from the hydraulic fracturing. We use a dislocation-based analytical model to simulate multistage hydraulic fracturing of three horizontal wells at a single well pad to explore the spatiotemporal evolution of total stress perturbations. Results show that the number and distribution of fracturing stages affect both the distribution and magnitude of stress changes and that the stress change diminishes with distance. The undrained injection-induced stress change is below 10 -3   MPa  at distances ≥1 km for first-stage fracturing but reach 10 -1   MPa for multistage fracturing of 30 stages in three wells. Undrained stress changes scale linearly with the magnitude of fluid leakoff into the formation – halving the effective fracture width halves the induced stress magnitudes and with an identical distribution – limiting the potential for fault reactivation. Scaling analysis for pressure diffusion distal from the reservoir indicate that the short-term impact is indeed essentially undrained. Estimates for long-term depletion identify a similar induced stress signal of opposite sign but with similar Coulomb potential for reactivation in the long-term. Such magnitudes of Coulomb stress changes suggest the possibility of fault reactivation on critically-stressed faults at kilometer separation from the injection both in the short-term due to stimulation and in the long-term resulting from depletion. Highlights: A dislocation theory based model defines the spatiotemporal evolution of stress perturbations after hydraulic fracturing. Multistage fracturing accumulates a stress perturbation with a maximum amplitude of ~0.1 MPa at a distance of 1 km . Fracturing as a single well pad can result in a Coulomb failure stress capable of reactivating critically-stressed faults.